Determination of tellurium by continuous hydride generation and atomic fluorescence spectrometry - El-Hadri, Faouzia; Morales Rubio, íngel; de la Guardia, Miguel (Ciencia, 1970)
It has been developed a simple method for the determination of Te(IV) and total tellurium in environmental samples by hydride generation and atomic fluorescence spectrometry (HGAFS). For Te(IV) determination, acidified samples, aspirated in a carrier of 5 mol/L HCl, were merged with a NaBH4 1.2%(m/v) solution, with sample and NaBH4 flow rates of 9.8 and 3.1 mL/min respectively. The hydride generated in a 100 cm reaction coil was passed through a gas-liquid separator and transported to the detector with an Ar flow of 400 mL/min. For total tellurium determination samples were heated, 10 min in a water bath at 60°C, after addition of 1.0 g NaBr to reduce Te(VI) to Te(IV). Solid NaBr was employed to avoid a long reduction step and the dilution of samples. The determination of total tellurium by atomic fluorescence was carried out as described above and Te(VI) was calculated as the difference between total tellurium and Te(IV). The limit of detection values obtained were between 0.4 and 0.7 Î¼g/L and the calibration graph was linear up to 20 Î¼g/L of tellurium. Recovery studies of different spiked concentrations of Te(IV) and Te(VI) in natural water samples were between 98 and 105% for Te(IV) and 99 to 109% for total tellurium. Furthermore, accuracy of the method was evaluated by using a sediment reference material with a known amount of tellurium after its leaching by means microwave treatment with 3 mol/L HCl.